Emotional processing during psychotherapy among women newly diagnosed with a gynecological cancer. Issue 4 (14th December 2016) - Manne, Sharon L.; Myers-Virtue, Shannon; Darabos, Katie; Ozga, Melissa; Heckman, Carolyn; Kissane, David; Rotter, David
Abstract: Objective: Our aim was to compare changes in emotional processing by women newly diagnosed with gynecological cancer enrolled in either a coping and communication skills intervention (CCI) or a supportive counseling (SC) intervention. We examined the association between in-session emotional processing and patient-rated therapeutic progress. Method: Three therapy sessions with 201 patients were rated for the depth of emotional processing (peak and mode) during emotion episodes (EEs) using the Experiencing Rating Scale (EXP). Participants completed measures of dispositional emotional expressivity, depressive symptoms, and cancer-related distress before treatment began, as well as ratings of perceived progress in therapy after each session. Results: Peak EXP ratings averaged between 2.7 and 3.1, indicating that women discussed events, their emotional reactions, and their private experiences in sessions. A small proportion of patients had high levels of processing, indicating deeper exploration of the meaning of their feelings and experiences. Women in SC were able to achieve a higher level of emotional processing during the middle and later sessions, and during cancer-related EEs in the later session. However, emotional processing was not significantly associated with a patient's perceived therapeutic progress with SC. In the CCI group, higher levels of emotional processing were associated with greater session progress, suggesting that it may play an important role in patient-rated treatment outcomes. Significance of results: Newly diagnosed gynecological cancer patients are able to attend to their emotions and personal experiences, particularly when discussing cancer-related issues during both short-term SC and prescriptive coping skills interventions.